Are impairments of time perception in schizophrenia a neglected phenomenon? - Bonnot, Olivier; Montalembert, Marie de; Kermarrec, Solenn; Botbol, Michel; Walter, Michel; Coulon, Nathalie (Journal of physiology, Paris, 2011)
► Discrimination and the reproduction of durations are impaired in schizophrenia. ► The cognitive temporal processor is dedicated to time perception process. ► Time units are accumulated and counted to determines the length of an interval. ► Time perception impairment may be related to attentional and memory processes. ► Time perception may have an etiopathogenic role in schizophrenia. Based on clinical, phenomenological and neurobiological observations, psychiatrists often report a deficit in time estimation in patients with schizophrenia. Cognitive models of time estimation in healthy subjects have been proposed and developed for approximately 30 years. The current theory in the field of time perception, which is supported by a connectionist model, postulates that temporal judgement is based upon a pacemaker–counter device that depends mostly upon memory and attentional resources. The pacemaker emits pulses that are accumulated in a counter, and the number of pulses determines the perceived length of an interval. Patients with schizophrenia are known to display attentional and memory dysfunctions. Moreover, dopamine regulation mechanisms are involved in both the temporal perception processes and schizophrenia. Thus, it is still unclear if temporal impairments in schizophrenia are related to a specific disturbance in central temporal processes or are due to certain cognitive problems, such as attentional and memory dysfunctions, or biological abnormalities. The authors present a critical literature review on time perception in schizophrenia that covers topics from psychopathology to neuroscience. Temporal perception appears to play a key role in schizophrenia and to be partially neglected in the current literature. Future research is required to better ascertain the underlying mechanisms of time perception impairments in schizophrenia.